Adsorption of the H and H2O on SnO2 Surfaces in an O2 Environment: Density Functional Theory Study - H. Zakaryan
Hydrogen, oxygen and water have huge impact on gas sensing mechanisms in the environment. This research related to the H and H2O adsorption on the SnO2 – (110), (100), (101), (001) surfaces under different O2 conditions. A lot of experimental and theoretical study was done previously to explain SnO2 gas sensors behavior in the environment, but atomic size processes remain unclear. Density functional theory is usedto investigate adsorption on all possible surfaces and reconstructions in the different O2 conditions. Environment conditions were simulated using atomistic thermodynamics. Calculations in this studyconfirm that water tends to dissociate on all surfaces in an oxygen reach surface, but not on reduced one.
Keywords: Physics; Materials science